The role of ancient palaces in activating tourism within urban settings in Algeria - Case study of Qasr Al-Shalala Tiaret - Farida, Saci; Boudjemaa, Khalfallah (Technium Social Sciences Journal, 2023)
Some of the ancient Algerian cities represent purely historical landmarks that highlight the historical backgrounds of successive civilizations, and with the observed variation in the climatic zones that resulted in the emergence of desert palaces, and are a living example of human adaptation and adaptation to the peculiarities of the region in which they grew up, The palaces are a cultural heritage that reflects the effects of past generations and an urban heritage that expresses to a large degree the specificity that distinguishes the population from the interdependence, values and customs, among these palaces is Al-Shalala Dhahrania. Palace as a stand-alone example through the episodes of history, which represents the first nucleus of its development and emergence. However, what is noticeable about this urban pattern is that it is witnessing great deterioration and neglect due to many changes, some of which are climatic and some of which are due to the random intervention of humans, which in turn affected the specificities of the region.